The phenomenon of begging in the comment columns of public figures’ Instagram account viewed by the lens of Media Ecology Theory - Siregar, Rafiqah Yusna; Mazdalifah, Mazdalifah; Sembiring, Sri Ulina Br (Priviet Social Sciences Journal, 2025)
The phenomenon of digital begging in Instagram comments by public figures reflects changing patterns of social interaction influenced by digital media. This study aims to analyze the practice of openly asking for help on social media through the lens of McLuhan's media ecology theory. Using a descriptive qualitative approach, this study combines thematic and critical discourse analyses of netizen comments directed at seven Indonesian public figures with a luxurious lifestyle. The analysis shows that these comments form a discourse pattern that emphasizes the glorification of wealth, emotional dependence, representations of suffering, and the legitimacy of public pleas. Media, in this case, Instagram, functions as a symbolic environment that shapes perceptions, behaviors, and social values. This study offers novelty by revealing the dark side of social media as a mediating space for economic hope and parasocial interaction while also highlighting the changing power relations between public figures and digital society. These findings broaden our understanding of the impact of media ecology on shaping communication culture in the platform era.